PERAN PEMERINTAH KOTA CILEGON DAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) CILEGON DALAM MENCEGAH TINDAKAN INTOLERANSI ANTAR UMAT BERAGAMA - Muhammad Abdul Aziz; Ratna Sari Dewi; Dinar Sugiana Fitrayadi (Program Studi Ilmu Pemerintahan, 2024)
This research aims to investigate how the Cilegon City Government and the Forum for Interfaith Harmony (FKUB) collaborate in designing, implementing, and evaluating programs to maintain interfaith harmony and prevent religious intolerance. Data were collected through policy document analysis and in-depth interviews with officials from Kesbangpol, FKUB, and the Cilegon City Ministry of Religious Affairs Office using a qualitative descriptive technique. The conclusions drawn from this study include goal-setting techniques, formulation of the existing situation, identification of barriers and facilitators, and development of activity plans. Implementation of the program involves disseminating regulations, convening meetings with religious leaders, establishing youth forums, and organizing interfaith community coordination meetings. According to program evaluation, the interfaith harmony index for Cilegon City in 2022 achieved a score of 79.71 points, surpassing the target of 68.74 points and also exceeding the national average interfaith harmony index of 72.39 points. These findings imply the potential to enhance understanding and preventive actions in promoting harmony among religious communities.